eCurriculum and Online Assessment in Clinical Pharmacology & Toxicology: Developing a Virtual OSCE for Medical Students - Holbrook, Anne; Keshavjee, Karim; Telford, Victoria; Vidug, Kristina; Profetto, Jason; Levinson, Anthony J (My University, 2022)
E-learning and online resources for Canadian medical students could be one of the most beneficial learning tools in this day and age. Limited expert faculty numbers and training in Clinical Pharmacology and Toxicology (CPT) and the current pandemic have driven us to develop processes and evaluation metrics for an online Observed Structured Clinical Exam (OSCE) in CPT.
Keywords: OSCE; medical curriculum; virtual OSCE; e-learning